2016
DOI: 10.1016/j.krcp.2016.05.005
|View full text |Cite
|
Sign up to set email alerts
|

High-level viruria as a screening tool for BK virus nephropathy in renal transplant recipients

Abstract: BackgroundAlthough early monitoring of BK virus infection in renal transplant patients has led to improved outcomes over the past decade, it remains unclear whether monitoring for viremia is the best screening tool for BK virus nephropathy (BKVN).MethodsWe conducted a retrospective review of the medical records of 368 renal transplant recipients who had a minimum of 18 months of posttransplantation follow-up. The relationship between the presence of BK viruria and a composite end point of BK viremia/BKVN was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…Therapeutic strategies often promote resolution of infection and prevent further decline in the kidney allograft function, but the damage from BKVN may not be reversed, leading to chronic allograft dysfunction [1]. In fact, the results demonstrated that even after strategies had been implemented, a significant percentage of patients had progressive allograft dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therapeutic strategies often promote resolution of infection and prevent further decline in the kidney allograft function, but the damage from BKVN may not be reversed, leading to chronic allograft dysfunction [1]. In fact, the results demonstrated that even after strategies had been implemented, a significant percentage of patients had progressive allograft dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…B K VIRUS (BKV) is a non-enveloped DNA virus of the polyomaviridae family, and 80% to 90% of the general population is seropositive for BKV [1]. Primary infection usually occurs in the first decade of life, probably by respiratory or oral transmission, and then becomes latent mainly in the urinary tract [2].…”
mentioning
confidence: 99%
“…At the minimum, high levels of PCR-BKV viruria (≥2.5 x 10 7 copies/mL) may be an early marker of BKV viraemia or BKVN (ref. 54 ). If BKV viruria develops in early post-transplant period, risk for BKVN development is higher compared to later occurrence.…”
Section: Bkv Viruriamentioning
confidence: 99%
“…Approximately 30% to 60% of post-transplant recipient has developed BK viruria, and 10% to 20% has BK viremia (11). About 1% to 10% has developed BK-VAN during the first year after transplant (5,12,13). During BK virus replication, BK viruria usually precedes BK viremia by a median of ~4 weeks.…”
Section: Burden Of Bk Virus In Kidney Transplant Recipientmentioning
confidence: 99%